2012
DOI: 10.1063/1.4755995
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorbance of doped Si quantum dots calculated by time-dependent density functional theory with partial electronic self-interaction corrections

Abstract: The optical properties of Si quantum dots (QDs) with phosphorous and aluminum dopants have been calculated with the recently tested Heyd-Scuseria-Ernzerhof (HSE) density functionals to ascertain the effect of functional corrections to electronic self-interaction. New results have been obtained for 20 crystalline and amorphous structures of Si(29) and Si(35) quantum dots and are compared to our previous results obtained using the PW91∕PW91 functionals. The bandgaps are greater in magnitude and shifted to higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…1 However, bulk Si exhibits an indirect band gap which limits its optical absorption efficiency. [15][16][17][18][19] However, most of these studies are based on the bulk-truncated structures. There have been a large number of investigations on the properties of the doped and undoped Si NCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, bulk Si exhibits an indirect band gap which limits its optical absorption efficiency. [15][16][17][18][19] However, most of these studies are based on the bulk-truncated structures. There have been a large number of investigations on the properties of the doped and undoped Si NCs.…”
Section: Introductionmentioning
confidence: 99%
“…17 17 Pi et al showed that the Si nanocrystals above 4 nm have localized surface plasma resonance (LSPR) effect when they are doped with more than 10 P atoms. In order to study their electronic and optical properties, the surfaces of Si NCs are generally passivated with hydrogen, halogen and hydroxyl, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Such silicon nanoscale materials have been termed nanoclusters (NCs), nanocrystals, nanodots, or quantum dots. [16][17][18][19][20][21] Using first-principles calculations, Wang et al 16 investigated the size dependence of the optical properties of the spherical and cylindrical hydrogenpassivated Si nanoparticles, and their findings revealed that the band gap increases and the associated absorption spectrum exhibits a blue shift with the decrease in the diameter of the spheres or cylinders. 1 Therefore, the size and shape control of nanomaterials can provide a new way to tune the physical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum displacement was set as 1.8×10 -3 Å. Then, the optical properties were calculated by time-dependent density-functional theory (TDDFT) [48] at B3LYP/6-31G implemented in Gaussian 09 software package [49].…”
Section: Ge45h48mentioning
confidence: 99%
“…Experiment [11] shows that amorphous Si nanoparticles have stronger optical absorption than those with higher crystallinity, especially in short wavelength region. Theoretical calculations also show that the absorption spectra of non-crystalline silicon nanoclusters exhibit a red-shift compared to those of crystalline silicon structures, and doping P and Al can cause the spectrum to shift even further toward the red region [12,13]. Furthermore, localized surface plasma resonance (LSPR) can be produced when more than 10 P atoms are doped in a Si nanocrystal of 1.8 -4 nm [14].…”
Section: Introductionmentioning
confidence: 98%